Stealth Disclosure of Accounting Restatements - Files, Rebecca; Swanson, Edward P.; Tse, Senyo (The Accounting review, 2009)
Managers exercise considerable discretion over how they announce an accounting restatement in a press release. Some firms issue a press release that discloses the restatement in the headline (high prominence). Others provide a press release with a headline on a different subject (for example, earnings news) but describe the restatement in the body of the release (medium prominence). The remaining firms discuss the restatement at the end of the press release in a footnote to operating results (low prominence). Mean three-day returns differ considerably across these three categories of prominence (−8.3, −4.0, and −1.5 percent, respectively). We find that disclosure prominence is significantly negatively associated with returns in a model that controls for the seriousness of the GAAP violation, restatement magnitude, other restatement characteristics, and potential endogeneity. Similarly, we find the likelihood of class action lawsuits is significantly reduced with less prominent disclosure.